2006
DOI: 10.1002/cem.988
|View full text |Cite
|
Sign up to set email alerts
|

Common components and specific weight analysis and multiple co‐inertia analysis applied to the coupling of several measurement techniques

Abstract: The present paper compares two multiblock techniques: the Common Components and Specific Weights Analysis (CCSWA) and the Multiple Co-inertia Analysis (MCoA). Both methods are used to (1) to investigate the relationships among various data tables and (2) to extract latent variables from information of different nature, reflecting different facets of a food product. Our objective is to study the ability of these methods to extract, from a set of data tables, latent characteristics which are representative of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…It was also successfully applied in several domains of application and in particular in chemometrics. For a more recent investigation of CCSWA, we refer to Mazerolles et al [15] and Hanafi et al [4,16].…”
Section: Equivalence Between Hpca and Ccswa And Their Relation To Indmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also successfully applied in several domains of application and in particular in chemometrics. For a more recent investigation of CCSWA, we refer to Mazerolles et al [15] and Hanafi et al [4,16].…”
Section: Equivalence Between Hpca and Ccswa And Their Relation To Indmentioning
confidence: 99%
“…We refer to a paper by Janné et al [19] for an application of HPCA within the framework of spectroscopic data. CCSWA was applied for the coupling of several instrumental measurements [4,15,23]. We herein use a simple case study pertaining to sensory profiling to illustrate the methods of analysis and we aim at focusing on the complementarities of HPCA and CCSWA.…”
Section: Simple Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In later studies CCSWA was successfully applied to different data sets of food products [20][21][22][23] as well as food packaging materials [24]. The results have shown that CCSWA extracts relevant information more efficiently than classical single-block chemometric approaches [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that CCSWA extracts relevant information more efficiently than classical single-block chemometric approaches [20,24]. However, in all these studies CCSWA was used as an exploratory tool and not for prediction of class membership of new samples [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%